The effect of non-recurring items on analysts' earnings forecasts - Nan Li; Hongtong Su; Wanqing Dong; Kai Zhu (China Journal of Accounting Research, 2018)
This article discusses the effects of non-recurring profits and losses on statement users' decision-making processes from the perspective of securities analysts. We examine the relationship between analysts' forecast revisions and firms' non-recurring earnings. We find that 1) non-recurring gains and losses can influence analysts' earnings forecast revision; 2) compared with non-recurring items resulting from policy changes, analysts are more concerned about those attributed to changes in business scope; 3) if listed companies use non-recurring items to turn losses into gains during earnings management, it will weaken the effects of non-recurring items on analysts' earnings forecast revision. The results suggest that non-recurring items that result from changes in business scope incorporate information that users need for the future operation of the business. This article verifies the information relevance of non-recurring items and provides evidence for the necessity of non-recurring item disclosure.
Keywords: 650; Non-recurring items; Earnings forecasts; Revisions